DEVELOPMENT OF A SOFTWARE CONTROLLER FOR THE AUTOMATED CREATION AND MANAGEMENT OF VIRTUAL RESOURCES FOR RUNNERS - Yu. Korchak; B. Mikh; Yuriy Furgala (Електроніка та інформаційні технології)
The work developed a functional model (prototype) of the controller for the automated creation and management of runners’ virtual computing resources. The analysis of potential technologies for its implementation determined the choice of a combination of RPC, cRPC, HTTP/2 and Go technologies with the protobuff serializer, which meets all modern requirements for a distributed system’s speed, efficiency and scalability. It has been experimentally proven that the RPC protocol can serve as a reliable interface for managing resources in virtual environments, providing convenience and efficient integration with CI/CD systems. Using test scenarios made it possible to reflect actual operating conditions and integration testing and, as a result, evaluate the interaction between the MVP and other system components.